Melukis Harapan di Atas Pasir Waktu: Sosialisasi dan Pelatihan Softskill Guru Berbasis Microteaching di SDN 01 Saonek, Raja Ampat - Andi Maryam; Ainun Mardiah; Yuni Riskita Mangopo; Heriyanti Tahang; Rizky Ekawaty Ahmad; Sulkipli M; Irfandi Idris; Jenro P Sijabat; Abdul Mu’thy (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
Soft skills are essential competencies that teachers must possess to create an effective, communicative, and student-centered learning process. However, the geographical conditions of SD Negeri 01 Saonek, which is located in an island area, present unique challenges, particularly related to limited access to travel outside the island and unstable communication networks. These limitations have resulted in teachers at the school not receiving adequate training in soft skill development, including communication, classroom management, and self-reflection abilities. To address this need, a socialization and training program based on microteaching was implemented as an effort to enhance teachers’ professional competencies. The microteaching method was chosen because it provides opportunities for direct practice, structured feedback, and simplified yet effective teaching simulations. The training was designed to help teachers understand good teaching techniques, build confidence, and strengthen interpersonal skills in instructional interactions. In addition, the collective feedback sessions offered participants chances to learn from one another and improve their teaching strategies based on peer observations. The results of the activity indicated an improvement in teachers’ ability to design lesson scenarios, manage classrooms, deliver material more clearly, and communicate more effectively with students. Teachers also reported increased motivation and a deeper understanding of the importance of soft skills in supporting their professionalism. Thus, the microteaching training provided new insights into the capacity-building process for teachers at SD Negeri 01 Saonek and served as a relevant solution for island schools facing limited access to conventional training. This program is expected to continue and become a model for empowering teachers in 3T regions to sustainably improve education quality.